THE ROLE OF NUMERICCA 29 CAFÉ IN SHAPING URBAN SOCIAL IDENTITY - Alhusna Fil Azari Syamsur. S; Darman Manda; Dyan Paramitha Darmayanti (Universitas Negeri Makassar, 2026)
Urban social spaces have become an important arena for shaping the identity of modern society. This study aims to examine the role of Kafe Numericca 29 in shaping the social identity of urban communities in Makassar City, emphasizing that modern cafes serve not only as places of consumption but also as dynamic social and cultural spaces. This study uses a qualitative case study approach, with data collected through participatory observation, in-depth interviews with seven informants aged 21–50 years, and documentation of cafe activities and social media. The results show that Numericca 29 Cafe has four main roles in the construction of urban community social identity. First, as a symbol of status and lifestyle, this cafe serves as a medium for expressing modernity and social prestige through visitors' behavior, appearance, and digital representation. Second, as a space for social interaction, Numericca 29 helps strengthen inclusiveness, emotional attachment, and collective solidarity through various community and cultural activities. Third, in the context of institutional identity management strategies, the management consciously creates a comfortable, open, and friendly atmosphere, both in physical spaces and through digital media. Fourth, as a third place, this cafe becomes a social space that balances the demands of modernity and human needs for togetherness and a sense of belonging. Overall, Numericca 29 Café has transformed into an urban social institution that harmonizes modern lifestyles, cultural expressions, and social cohesion. These findings show that public spaces such as cafés play an important role in shaping social identity, strengthening community relations, and reflecting the cultural dynamics of today's urban Makassar society.